Predictive Factors of Mortality in Pediatric Pleuropulmonary Blastoma: A Surveillance Epidemiology and End Results Database Analysis - Abhilasha Borad; Ellie Deianni; Sathyaprasad Burjonrappa (Wolters Kluwer Medknow Publications, 2024)
Purpose: Pleuropulmonary blastoma (PPB) is a rare malignancy associated with mutations in the DICER1 gene. Early-stage disease (PPB type I) mimics cystic lung malformations and develops in infants <1 year of age, and PPB type II and III arises in older children. The objective of this study was to analyze predictive factors of mortality in pediatric patients aged 0-19 years diagnosed with PPB between 2000 and 2019 in the USA. Methods: A retrospective analysis of pediatric patients (0-19 years) in the Surveillance Epidemiology and End Results database was conducted from 2000 to 2019 with a diagnosis of PPB using International Classification of Disease for Oncology, third edition code 8973/3 and rare tumor code 45. Demographics, incidence, staging, treatment, and mortality were extracted. A mortality risk predictive equation was developed using logistic regression. Statistical analysis was conducted through Microsoft Excel Analysis ToolPak and Solver. Results: There were a total of 71 new cases of PPB during the study period, with 16 (22%) deaths. The demographic analysis demonstrated that 40/71 (56.3%) patients were female, 57/71 (80.3%) were White, and 64/71 (90.1%) resided in metropolitan areas. Regression analysis demonstrated a statistically significant correlation between mortality and stage (P = 0.029), need for chemotherapy (P = 0.047), and female sex (P = 0.019). There was no significant correlation between mortality and need for radiation, race, or age at diagnosis. Multiple logistic regression analysis generated a predictive equation of mortality dependent on the stage of PPB, need for chemotherapy, and sex. This equation has an 82% accuracy, 81% sensitivity, and an 18% false positive rate. Conclusion: PPB is a rare disease. Distinguishing PPB from benign cystic lung malformations in infancy is important to avoid progression to Type II and III PPB. Advanced stages of PPB have a greater need for systemic chemotherapy and radiation with a poor prognosis.